Skills matter : further results from the survey of adult skills. - Organização para a Cooperação e Desenvolvimento Econômico (Paris : OECD, 2016)
In the wake of the technological revolution that began in the last decades of the 20th century, labor market demand for information-processing and other high-level cognitive and interpersonal skills is growing substantially. The Survey of Adult Skills, a product of the OECD Program for the International Assessment of Adult Competencies (PIAAC), was designed to provide insights into the availability of some of these key skills in society and how they are used at work and at home. The first survey of its kind, it directly measures proficiency in several information-processing skills -- namely literacy, numeracy and problem solving in technology-rich environments. This volume reports results from the 24 countries and regions that participated in the first round of the survey in 2011-12 (first published in OECD Skills Outlook 2013: First Results from the Survey of Adult Skills) and from the nine additional countries that participated in the second round in 2014-15 (Chile, Greece, Indonesia [Jakarta], Israel, Lithuania, New Zealand, Singapore, Slovenia and Turkey). It describes adults' proficiency in the three information-processing skills assessed, and examines how skills proficiency is related to labor market and social outcomes. Another related report, The Survey of Adult Skills: Reader's Companion, Second Edition, describes the design and methodology of the survey and its relationship to other international assessments of young students and adults. 1. Overview: why skills matter -- 2. Adults' proficiency in key information-processing skills -- 3. The socio-demographic distribution of key information-processing skills -- 4. How skills are used in the workplace -- 5. The outcomes of investment in skills. In the wake of the technological revolution that began in the last decades of the 20th century, labor market demand for information-processing and other high-level cognitive and interpersonal skills is growing substantially. The Survey of Adult Skills, a product of the OECD Program for the International Assessment of Adult Competencies (PIAAC), was designed to provide insights into the availability of some of these key skills in society and how they are used at work and at home. The first survey of its kind, it directly measures proficiency in several information-processing skills -- namely literacy, numeracy and problem solving in technology-rich environments. This volume reports results from the 24 countries and regions that participated in the first round of the survey in 2011-12 (first published in OECD Skills Outlook 2013: First Results from the Survey of Adult Skills) and from the nine additional countries that participated in the second round in 2014-15 (Chile, Greece, Indonesia [Jakarta], Israel, Lithuania, New Zealand, Singapore, Slovenia and Turkey). It describes adults' proficiency in the three information-processing skills assessed, and examines how skills proficiency is related to labor market and social outcomes. Another related report, The Survey of Adult Skills: Reader's Companion, Second Edition, describes the design and methodology of the survey and its relationship to other international assessments of young students and adults.